Properties of silica from rice husk and rice husk ash and their utilization for zeolite y synthesis - Saceda,Jan-Jezreel F. (2011)
This study compared properties of silica (SiO2) from rice husk (RH) and rice husk ash (RHA) extracted by acid- and heat-treatment. The SiO2 from RH was in amorphous phase with nearly 100% purity while that from RHA was in crystalline phase with 97.56% purity. Both extracted SiO2 were used in the synthesis of zeolite NaY but that from RH was better due to the efficiency in product recovery and simplicity of extraction. After the NaY was exchanged to NH4Y and calcined to convert to HY, the product did not carry over the textural properties of the parent NaY and NH4Y.